The Categorization of Occupation in Identified Skeletal Collections: A Source of Bias - Cardoso, Francisca Alves (2012)
Identified skeletal collections, i.e .skeletons for which sex, age at death and occupation at death are known, have been used to test methods for recording entheseal changes (EC). By testing methods on identified collections the sensitivity of EC for recording activity levels can be ascertained prior to applying the methods to test hypotheses in archaeological contexts. However, the definition of occupational categories used for this research may, in itself, be a source of bias. The aim in this study was to test how categorizing occupation affected the interpretation of EC. Male skeletons (n=211) from two Portuguese identified skeletal collections were used. Three methods for categorizing occupations, all of which have been previously published, were used each dividing occupations into 5, 3 and 2 categories, respectively. Fibrocartilaginous entheses were recorded and EC scored as present/absent. Results showed that the method for categorizing occupation affected the frequencies of EC found in occupational categories for specific entheses. Frequencies which were significantly different between occupational categories for one method were not necessarily significant for others. This demonstrates that the sensitivity of the occupational categorization does affect the results. However, using logistic regression age was found to have a greater effect than occupation. These results demonstrate the need for standardized occupational categories, as well as the importance of considering age.